PENGENALAN BAHASA JAWA PADA ANAK USIA DINI MELALUI PEMBIASAAN CIRCLE TIME - Setyowati, Linda; Rahmawati, Ida Yeni; Wahyudi, Wahyudi (Jurnal Ilmiah POTENSIA, 2025)
Javanese is one of Indonesia's regional languages facing near extinction. Therefore, introducing Javanese from an early age is crucial for preserving noble cultural values. PAUD Sabila Ponorogo implements early Javanese language introduction through Circle Time activities. This research aims to describe the implementation and identify challenges in introducing Javanese to early childhood through Circle Time activities. A qualitative research approach was employed for this study. Data were collected through observation, interviews, and documentation. The findings indicate that Javanese language introduction at PAUD Sabila Ponorogo focuses on three main areas: Javanese vocabulary, traditional children's songs (tembang dolanan), and etiquette or manners (unggah-ungguh) in daily interactions. The learning process is well-structured through systematically designed teaching modules aligned with learning themes. Each session targets the introduction of at least 10 new vocabulary words consistently presented to children in every meeting. However, the implementation faces both technical and non-technical challenges for teachers and the school. Despite these obstacles, teachers and the school have successfully addressed emerging problems by adapting teaching strategies and conducting continuous evaluations to enhance the effectiveness of Javanese language learning at PAUD Sabila Ponorogo.